DETEKSI DINI PREEKLAMSI PADA IBU HAMIL DENGAN PENIMBANGAN BERAT BADAN DAN PENGUKURAN TEKANAN DARAH - Iin Setiawati; Siti Rochimatul Lailiyah (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2020)
Preeclampsia is a condition that occurs in pregnancy characterized by hypertension accompanied by proteinuria accompanied by edema due to pregnancy after 20 weeks or immediately after delivery. Based on data from the East Java Health Office, the mortality rate in East Java has decreased from 2010-2018 from 598 to 370 maternal deaths. The cause of maternal death in East Java in 2018 was 31% preeclampsia / eclampsia, 22% bleeding, 10% heart, 4% infection and others 33% and 68.65% occurred at the reproductive age of 20-34 years. The community service method is by collecting data on pregnant women with local midwives at PMB Sumarti, SST in Kapor Village, Burneh Bangkalan, after which all pregnant women collect on a predetermined day and explain the objectives of community service and provide counseling about preeclampsia to pregnant women, continued weighing, measuring height and measuring Body Mass Index (BMI), measuring blood pressure in pregnant women through ROT and MAP Based on the results obtained from 16 pregnant women who have a risk of preeclampsia, there are 3 people (18.75%) positive from the results of excessive BMI and MAP ≥90. Judging from the characteristics of pregnant women, BMI is excessive, and is more than 35 years old, while one person is primigravida.